Convergent and Divergent Pathways Decoding Hierarchical Additive Mechanisms in Treating Cerebral Ischemia–Reperfusion Injury. (19th December 2013) - Zhang, Ying‐Ying; Li, Hai‐Xia; Chen, Yin‐Ying; Fang, Hong; Yu, Ya‐Nan; Liu, Jun; Jing, Zhi‐Wei; Wang, Zhong; Wang, Yong‐Yan
Summary Introduction Cerebral ischemia is considered to be a highly complex disease resulting from the complicated interplay of multiple pathways. Disappointedly, most of the previous studies were limited to a single gene or a single pathway. The extent to which all involved pathways are translated into fusing mechanisms of a combination therapy is of fundamental importance. Aims We report an integrative strategy to reveal the additive mechanism that a combination (BJ) of compound baicalin (BA) and jasminoidin (JA) fights against cerebral ischemia based on variation of pathways and functional communities. Results We identified six pathways of BJ group that shared diverse additive index from 0.09 to 1, which assembled broad cross talks from seven pathways of BA and 16 pathways of JA both at horizontal and vertical levels. Besides a total of 60 overlapping functions as a robust integration background among the three groups based on significantly differential subnetworks, additive mechanism with strong confidence by networks altered functions. Conclusions These results provide strong evidence that the additive mechanism is more complex than previously appreciated, and an integrative analysis of pathways may suggest an important paradigm for revealing pharmacological mechanisms underlying drug combinations.